EXPLORING THE ROLE OF ISLAMIC EDUCATION IN SOCIAL CHANGE: THE IMPACT OF THE TAHFIDZ PROGRAM IN BAHRUL ULUM QUR'ANI ISLAMIC BOARDING SCHOOL - Ridwan, Ridwan; Habibi, Yuliana; Rahmawati, Niken (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: Islamic education at the Bahrul Ulum Qur'ani Islamic Boarding School implements the tahfidz program as an approach that combines memorisation of the Qur'an with an understanding of moral and ethical values. Purpose: This study aims to analyse the impact of the tahfidz program on the formation of character and social involvement of students. This study uses a descriptive qualitative approach to understand the social phenomena that occur at the Bahrul Ulum Qur'ani Islamic Boarding School in Pemalang related to the tahfidz program. Method: This research will focus on one specific aspect, namely, students who participate in the tahfidz program. The population is students registered at the Bahrul Ulum Qur'ani Islamic Boarding School in Pemalang who participate in the tahfidz program. The number of samples taken ranged from 15-25 students. The research instrument includes Semi-Structured Interviews. And observation by observing the learning process and activities outside the cottage, to get a broader context. And documentation includes: Teaching materials, activity notes, and reports on relevant pesantren activities. Meanwhile, Data Analysis consists of Data Transcription, which is converting interview recordings into written text to facilitate analysis. Coding by identifying themes or categories from the data obtained. Result: The results of this study show that the tahfidz program at the Bahrul Ulum Qur'ani Islamic Boarding School in Pemalang has a positive impact on the development of students' character and their involvement in social activities. Conclusion: the data showed that students who memorised the Qur'an tended to have stronger ethical values and behaved better in their social environment, which signified the integration of religious values into their daily lives.